Energy, economic and environmental (3E) aspects of internal heat exchanger for ORC geothermal power plants. (1st December 2017) - Mohammadzadeh Bina, Saeid; Jalilinasrabady, Saeid; Fujii, Hikari
Abstract: Installing Internal Heat Exchanger (IHE) after the turbine, can increase the effectiveness of heat exchange process and consequently plant efficiency in the Organic Rankin Cycles (ORCs). The main objective of this study is to investigate and also compare the energy, economic and environmental issues for two different configurations of geothermal binary cycles including conventional ORC and ORC with Internal Heat Exchanger (IHE-ORC). Energy-Economic-Environment (3E) models for both cycles were developed and a parametric study was conducted with respect to the maximum thermodynamic efficiencies and minimum cost rate. Evaporator pressure, superheating degree of the steam, the minimum pinch difference temperature in the evaporator and also condenser temperature were analyzed to obtain the optimal performance of the system. The aim of this study was to investigate the effect of IHE in binary cycles on the exergy destruction rates for all components and finding the most sensitive equipment to IHE. The results indicated that under optimized economic conditions, IHE-ORC had higher net power output (5245 vs. 5063 kW) with lower production cost. Furthermore, IHE-ORC, had superior energy and exergy efficiencies (16.82%, 59.71% vs. 14.13%, 52.2%). Additionally, IHE system was more environmental friendly and in comparison with conventional ORC, it can save the fuel consumption by 3.6% higher value and consequently about 3.6% reduces the CO2 emission more than conventional ORC. Graphical abstract: The radar graph shows the benefits of installing IHE for ORC geothermal power plants at 3 aspects of thermodynamic, economic and environmental performance. The new system results higher output and thermodynamic efficiencies under lower produce cost that causes more fuel consumption saving and CO2 emission reduction. Highlights: Thermo-Economic analysis was applied to two different arrangements of Organic Rankine Cycle. Thermodynamic efficiencies and total annual cost are optimized as objective functions. Optimum parameters for different cycles at optimal design are investigated. Grassman diagram is employed for showing the main places of exergy destruction. The environmental benefits of the two different cycles were conducted.